Online learning and online assessments: attitude change and students’ perceptions - Loi, Chek Kim; Ang, Magdalene Chooi Hwa (Secholian Publication, 2022)
The purpose of this paper is twofold. First, it is to examine 44 Malaysian undergraduate students’ attitude change towards online learning and online assessments during the Covid-19 pandemic. Second, it intends to explore students’ perception of the emergency online learning and online assessments. Technology Acceptance Model (TAM) by Davis (1989) is used as the framework to describe the factors that determine the acceptance of the use of computers and pertinent technologies in various technologies and user groups. The pretest and posttest questionnaire responses were based on participants’ learning experience in the previous and current semesters, respectively. The findings show that in general, there was a positive change of attitude toward both online learning and online assessments. The interview data reflect how external factors namely institutional support, new and useful knowledge and online skills, accessibility, computer self-efficacy and enjoyment possibly play a role in the students’ change of attitude. It can be deduced from the findings that e-learning usage during the pandemic was influenced by the attitude change which was in turn determined by the external factors.